Hepatotoxicity and Antioxidants: An overview - Fikry, Ebtehal Mohammad; Ahmed, Ahmady Yousef (Journal of Drug Delivery and Therapeutics, 2019)
The liver is responsible for several functions in the body including performing and controlling the homeostasis as well as nutrient and energy supply, metabolism and growth. It activates and inactivates exogenous and endogenous xenobiotics due to it has a defense mechanism but this sometimes inadequate, resulting in pathological conditions that influence the function and structure of the liver compartment leading to pathophysiological changes which may results in hepatotoxicity. It is the main reason for withdrawing of some drugs from marketing. Antioxidants are the substances those are present at low levels and significantly delay or prevent oxidation of the oxidizable substrate. They are one solution for controlling the hepatotoxicity. It is necessary to obtain a comprehensive article giving us overview information about hepatotoxicity and antioxidants relationship. Keywords: Hepatotoxicity – Antioxidants - Pathophysiological changes